Conceptions of Immigrant Integration and Racism Among Social Workers in Sweden. Issue 1 (2nd January 2017) - Eliassi, Barzoo
ABSTRACT: Drawing on 22 qualitative interviews with social workers in Sweden, this article analyzes how social workers conceive immigrant integration and racism and tackle racism within their institutions and the wider Swedish society. The majority of the white social workers framed integration in relation to cultural differences and denied or minimized the role of racism in structuring their services and the ethnic relations in Sweden. In contrast, social workers with immigrant backgrounds were less compromising in discussing racism and assumed it as a problem both for themselves as institutional actors and as immigrants in everyday life and institutional settings. Social institutions in Sweden have been important actors in endorsing equality and accommodating differences. However, it is of paramount importance for social justice-minded social workers to identify and unsettle those structures and discourses that enable racist and discriminatory policies and practices against those groups who are not viewed as "core" members of the Swedish society. The absence of anti-racist social work within Swedish social work is primarily related to the idea of color-blind welfare universalism that is assumed to transcend the particularity of the needs, experiences, and perspectives of different groups in Sweden. While integration is envisioned and framed as a political project of inclusion of non-white immigrants, it tends to become a political device through which hierarchies of belonging are constructed. Following such conception of integration, cultural/religious differences and equality are framed as conflicting where cultural conformity underpinned by assimilationist discourses becomes a requirement for political, social, and economic equality.